Arylalkylamine-, β-carboline-, quinolizine- and azecine-derived compounds and their in vitro interaction with the ionotropic 5-HT3 receptor: search for new lead structures - Enzensperger, Christoph; Lehmann, Jochen; von Schroetter, Katrin; Riyazi, Anja; Verspohl, Eugen J. (Arzneimittelforschung, 2010)
Specific Serotonin receptor agonists and antagonists are marketed with respect to various diseases, most prominently severe emesis. To identify new chemical classes with affinity for the serotonin 5-HT3 channel, several compounds were synthesized which can be structurally classified as arylalkylamines, azecines, quinolizines and β-carbolines. These were tested in three models: 1. direct effect on ileum (overall model for contracting or relaxant effect), 2. antiserotoninergic effects on rat ileum (crude serotonin model), 3. inhibitory effect on the 5-HT3 receptor channel complex expressed in N1E-115 cells (serotonin-induced [14C]guanidinium influx (specific model)). Key findings and conclusion: Several azecine-type compounds exhibit 5-HT3 receptor channel antagonistic properties at concentrations close to that of tropisetron (used as a positive control) and might serve as potential lead structures for the development of further 5-HT3 channel receptor antagonists.
Keywords: Azecine; β-Carboline; 5-HT3 receptor; Phenylalkylamine; Quinolizine